Deuteronomy and the Judaean Diaspora - Nicholson, Ernest W. 1938- (Oxford Oxford University Press, Incorporated, 2014)
Ernest Nicholson draws together and expands a collection of his writings on Deuteronomy, presenting his challenging thesis that the book derived from thinkers and writers who lived among the Judaean exiles in Babylonia in the sixth century, and in significant ways represents a break with pre-exilic Israelite religion.
Cover -- Contents -- Abbreviations -- Publisher's Acknowledgements -- Part I -- 1. Introduction -- 2. Josiah and the Priests of the High Places (2 Kings 23: 8a, 9) -- 3. Deuteronomy and the Babylonian Diaspora -- 4. Deuteronomy, the Prophets, and Scripture -- 5. The 'Law' of the King in Deuteronomy 17: 14-20 -- 6. 'Do not dare to set a foreigner over you': The King in Deuteronomy and 'The Great King' -- Part II -- 7. Story and History in the Old Testament -- 8. The Deuteronomistic Corpus: History or Story? A Response to John Van Seters -- Bibliography -- Index of Authors -- A -- B -- C -- D -- E -- F -- G -- H -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- V -- W -- Index of Sources.
Description based on publisher supplied metadata and other sources
Keywords: Bible. -- Deuteronomy -- Criticism, interpretation, etc; Electronic books